Evaluating European Food Safety Authority Protection Goals for Honeybees (Apis mellifera): What Do They Mean for Pollination?. (3rd August 2018) - Croft, Simon; Brown, Mike; Wilkins, Selwyn; Hart, Andy; Smith, Graham C
ABSTRACT: In recent years there has been growing concern regarding the sudden and unexplained failure of honeybee ( Apis mellifera ) colonies. Several factors have been suggested, including pesticides. In an effort to regulate their impact, guidance published by the European Food Safety Authority (EFSA) has recommended that the magnitude of effects on exposed colonies should not exceed 7% reduction in colony size after 2 brood cycles. However, fears have been raised regarding the practicality of measuring such a loss in the field. It is also unclear how this protection goal relates to maintaining the ecosystem services provided by bees, which we argue should be a primary objective for regulators. Here, we evaluate what these protection goals mean in relation to ecosystems performance using a computational colony model that incorporates mechanisms to simulate both lethal and sublethal pesticide effects. To these simulations, we apply a testing regime similar to that commonly used in field trials to produce standard assessment metrics. By relating these measures to losses in forager activity, we aim to identify which could be used as effective indicators of reduced ecoservice and to quantify acceptable limits below which performance can be maintained. Our findings show that loss of colony size is the best indicator of reduced ecoservice. Metrics that focus on specific colony functions such as increased brood or forager mortality are ineffective indicators for all types of simulated pesticide effects. At the levels of colony loss recommended by EFSA, using our default parameterization, we predict a loss of ecosystems performance of 3% to 4%. However, based on an extensive sensitivity analysis, it is clear that this estimate is subject to substantial uncertainty with losses under alternative parameterizations of up to 14%. Nevertheless, our model provides a valuable framework for assessing protection goals, allowing regulators to test relevant impacts and quantify their magnitude. Integr Environ Assess Manag 2018;14:750–758. © 2018 Crown Copyright and SETAC Key Points: A colony model was developed for simulating regulatory field trials of pesticide exposure on honeybees. The model was used to evaluate EFSA protection goals in terms of impact on ecosystem service. Of standard field metrics, colony loss is the only indicator of impaired ecosystem service. For a 7% colony loss, the model predicts maximum foraging losses of between 0% and 14%.